PERLINDUNGAN HUKUM TERHADAP PRIVASI KONSUMEN E-COMMERCE DITINJAU MENURUT HUKUM POSITIF DAN SIYASAH SYAR'IYAH - Adriani, Dwi; Maloko, Thahir; Larissa, Dea (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2024)
E-Commerce is currently an electronic trading that is growing very fast. It is possible that crimes can also be committed by irresponsible individuals regarding consumer privacy data. The purpose of this study, to determine the form of legal protection of consumer privacy in e-commerce according to positive law. Knowing the siyasah syar’iyah probisions on consumer privacy in e-commerce. This research is a qualitative research using syariah normative theological approach and juridical approach. Sources of data used are primary data and secondary data. And the data collection method used by the researcher is the document technique (library study). Based on the results in this study, the ITE law and other positive laws and regulations that have provided clarity and protection to consumer privacy have regulated electronic trading regulations so that consumers no langer feel worried about privacy data held in transactions. Electronic commerce according to the siyasah syar’iyah provisions may be carried out as long as it does not conflict with Islamic law. Because according to siyasah syar’iyah, the government has the power to determine everything as long as it is in accordance with Islamic law, including the law on consumer privacy protection. So the two laws, both positive law and siyasah syar’iyah, have provided legal protection for consumer privacy in e-commerce transactions.